A Study On The Influence Of Characteristics Of Organizational Culture To The Work Performance - Wagner, B.G. (Accounting Department,, 2005)
The discussion and analysis adopted the theory of Charles Hampden-Turner's organisational culture characteristics, which cover individual to culture (XI), reciprocal values (X2), cybernetic changes (X3), affirmation (X4), communications (X5), sense of continuity and identity (X6), coherent point of view (X7), rewarders of excellence (Xg), and following patterns (Xg).Â The sample is 26% of population applying the statistical instrument Multiple Regression to calculate the most determining (significant) variables to the employees' work performance,from four available departments of PT Singer Industries Indoensia. The study conveyed the findings that AFFIRMATION, SENSE OF CONTINUITY AND IDENTIY, and REWARDERS OF EXCELLENCE are the most significant variables to the work performance at PT Singer Industries Indonesia, Tbk.. The previous similar studies on organisational Structure conducted at PT Telkom, and PLN Pesero, Malang, utilising different supportive theories, are used as references.Â The findings of this research at PT Singer Industries Indonesia, Tbk. explained a strong correlation (82.2%) and variables explained 67.6% the work performance of the employees.Â The more sample size might explain more detailed correlation between the characteristics of organisational culture to the work performance.